The magnetic field in HD 161701, the only binary system identified to consist of an HgMn primary and an Ap secondary - Hubrig, S. (2014)
Recently, we performed a complete study of the SB2 system HD 161701 with an orbital period of 12.5 d, consisting of an HgMn primary and a classical Ap secondary. Since this is the first system identified with this particular combination of peculiar stars, a study of the presence of a magnetic field in both components is of considerable interest to astronomers studying stellar magnetism and the impact of the presence of a magnetic field in binary systems. Apart from HD 161701, only one other close binary systems with a magnetic Ap component, the system HD 98088, is currently known. Using high accuracy radial velocity planet searcher (HARPS) polarimetric spectra obtained on six consecutive nights, we detect in the Ap component a mean longitudinal magnetic field of up to 200 G varying in strength over the orbital/rotational period. The magnetic field behaviour in this component is closely related to the position of the primary component, exhibiting negative polarity. There was no detection of any longitudinal magnetic field with an upper limit of ?90 G in the primary. L81